2018
DOI: 10.3390/joitmc4040046
|View full text |Cite
|
Sign up to set email alerts
|

A Model and Empirical Study on the User’s Continuance Intention in Online China Brand Communities Based on Customer-Perceived Benefits

Abstract: Many Chinese companies have recently joined a trend to build their own online brand community, which is good for their corporate strategy and even for innovation, but with a high failure rate due to the low continuance intentions of users. In addition, related research is rare, especially for studies on the relationships between customer-perceived benefits, satisfaction, and the continuance intention of users. The objective of this study was to examine the existing relationships between three constructs: custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…Products that are presumed to provide high functional benefits lead to utilitarian attitudes, while products with high perceived newness lead to hedonic attitudes [48]. Recent research has shown that consumers are affected by an initial emotional response when they are exposed to innovation [54,55], especially within the information and communications technologies (ICT) field.…”
Section: Product Stagementioning
confidence: 99%
“…Products that are presumed to provide high functional benefits lead to utilitarian attitudes, while products with high perceived newness lead to hedonic attitudes [48]. Recent research has shown that consumers are affected by an initial emotional response when they are exposed to innovation [54,55], especially within the information and communications technologies (ICT) field.…”
Section: Product Stagementioning
confidence: 99%
“…Numerous literatures on technology acceptance (Abu-Al-Aish & Love, 2013; Briz-Ponce and García-Peñalvo, 2015; Calisir et al., 2014; Davis et al., 1992; Davis, 1989; Hamid et al., 2016; Hess et al., 2014; Mou, Shin and Cohen, 2017a, 2017b; Padilla-Meléndez et al., 2013). , continuance intention (Almaghrabi et al., 2011; Amoroso and Chen, 2017; Han et al., 2018; Susanto et al., 2016; Tella and Olasina, 2014; Tiyar and Khoshsima, 2015), usability standards (Bahn et al., 2007; Quesenbery, 2005; Traynor, 2011), etc. have been reviewed to identify the key usability factors.…”
Section: Introductionmentioning
confidence: 99%
“…Continuance intention has been the subject of substantial theoretical developments (Rahman et al., 2017) such as IS continuance (Almaghrabi et al., 2011; Amoroso and Chen, 2017; Han et al., 2018; Susanto et al., 2016; Tella and Olasina, 2014; Tiyar and Khoshsima, 2015) and post-adoption usage (Jia et al., 2016; Ong and Lin, 2016). Continuance intention reflects post adoption behaviour and intention of continue using an information system (Limayem and Cheung, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve better performance in a smart society, users should be recognized as having a changed and strengthened role, and reflected as subjects of the innovation system [7,9,11]. Social networking platforms such as Facebook and Twitter have helped users to establish personal networks.…”
Section: Aim Of the Studymentioning
confidence: 99%